Assessment of knowledge, attitude and perception of general public in Selangor towards counterfeit honey / Amirah Adhwani Jamari - Jamari, Amirah Adhwani (2014)
Although Malaysia is not a major producer, consumption of honey is common in Malaysia. The aim of current research is to investigate knowledge, attitude and perception in regards to counterfeit honey. The research objectives were reached by investigating a representative sample of subjects from three districts around Selangor. The instrument utilized was a questionnaire, which included questions on demographic, honey usage pattern and knowledge, attitude and perception on counterfeit honey. The reliability of instrument was assessed using Cronbach Alpha. The findings showed that the majority of respondents have low knowledge on counterfeit honey. There is a number of factors (place, gender, age, race and honey consumption) significantly influenced the knowledge, attitude and perception of respondents towards counterfeit honey. As such, there is a need to educate public about counterfeit honey so that they will be more knowledgeable and up to date particularly on this issue.